Emotional Experiences of Young Adults Who Have Experienced Interparental Conflicts - Si June, Loo; Lea Baranovich, Diana (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to explore and gain an in-depth understanding of the emotional experiences of young adults who have experienced interparental conflicts. Qualitative research using phenomenological research design was used to explore the emotional experiences encountered by 5 young adults who have experiences with interparental conflicts. To collect research data, the researcher perused 3 stages of in-depth interview sessions with each young adult. Other forms of data were also obtained through observations and participants’ journals. The method of data analysis was guided by a simplified version of Stevick-Colaizzi-Keen’s method as discussed by Moustakas (1994). Three common themes were found when the researcher analyzed the research data to investigate the emotional experiences of young adults who experienced interparental conflict. The three themes were: negative emotions, positive emotions, and lack of emotions. The outcome of this research provided additional insights to understand young adults’ emotional experiences when going through interparental conflicts. Implications of the study and recommendations for future researchers were discussed.